2022
DOI: 10.3389/fonc.2021.744667
|View full text |Cite
|
Sign up to set email alerts
|

Potential Metabolite Biomarkers for Early Detection of Stage-I Pancreatic Ductal Adenocarcinoma

Abstract: Background & ObjectivesPancreatic ductal adenocarcinoma remains an extremely malignant tumor having a poor prognosis. The 5-year survival rate of PDAC is related to its stage (about 80% for stage I vs 20% for other stages). However, detection of PDAC in an early stage is difficult due to the lack of effective screening methods. In this study, we aimed to construct a novel metabolic model for stage-I PDAC detection, using both serum and tissue samples.MethodsWe employed an untargeted technique, UHPLC-Q-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…Based on serum metabolomics, two studies observed reduced leucine levels in renal tumors and small cell lung cancer (SCLC), respectively ( 16 , 29 ). Consistent with these findings, patients with pancreatic ductal adenocarcinoma also had reduced levels of two isomers of leucine: isoleucine and ortholeucine ( 39 ). Decreased levels of BCAAs have also been detected in saliva samples from patients with cancer, including oral squamous cell carcinoma, lung cancer and thyroid cancer ( 38 , 41 , 42 ), implying vigorous catabolism of BCAAs in cancer cells to meet the energy requirements of biological macromolecules.…”
Section: Metabolomic Biomarkers For Cancer Screening and Diagnosissupporting
confidence: 55%
“…Based on serum metabolomics, two studies observed reduced leucine levels in renal tumors and small cell lung cancer (SCLC), respectively ( 16 , 29 ). Consistent with these findings, patients with pancreatic ductal adenocarcinoma also had reduced levels of two isomers of leucine: isoleucine and ortholeucine ( 39 ). Decreased levels of BCAAs have also been detected in saliva samples from patients with cancer, including oral squamous cell carcinoma, lung cancer and thyroid cancer ( 38 , 41 , 42 ), implying vigorous catabolism of BCAAs in cancer cells to meet the energy requirements of biological macromolecules.…”
Section: Metabolomic Biomarkers For Cancer Screening and Diagnosissupporting
confidence: 55%
“…Lately, the utilization of mass spectrometry-based techniques to detect metabolic profiles in blood has emerged as a selective and sensitive tool to improve diagnosis of malignant diseases, including several types of cancers (such as colorectal, gastroenterological or pancreatic cancers) [25][26][27][28]. Specifically, metabolomic analyses of BC have widely demonstrated that metabolic dysregulation in cancer might be detected in a simple and cost-effective manner which may yield potential biomarkers of the disease behavior after further validation.…”
Section: Discussionmentioning
confidence: 99%
“…Pancreatic cancer, the deadliest and malignant cancers as a consequence of the difficulty to identify it in early stages [ 71 ], is also influenced by SIRTs activity and expression. SIRT5 expression is directly correlated to positive prognosis, as its loss promotes glutamic-oxaloacetic transaminase 1 (GOT1) acetylation, thus promoting cell proliferation by enhancing glutamine and glutathione metabolism [ 72 ].…”
Section: Sirtuins and Cancermentioning
confidence: 99%